Challenges and Open Issues in Transcatheter Mitral Valve Implantation: Smooth Seas Do Not Make Skillful Sailors - Russo, Giulio; Maisano, Francesco; Massaro, Gianluca; Terlizzese, Giuseppe; Mariano, Enrica; Bonanni, Michela; Matteucci, Andrea; Bezzeccheri, Andrea; Benedetto, Daniela; Chiricolo, Gaetano; Martuscelli, Eugenio; Sangiorgi, Giuseppe Massimo (Frontiers in Cardiovascular Medicine, 2022)
According to the European and American guidelines, surgery represents the treatment of choice for mitral valve (MV) disease. However, a number of patients are deemed unsuitable for surgery due to a prohibitive/high operative risk. In such cases, transcatheter therapies aiming at MV repair have been proven to be a valuable alternative and have been recently introduced in the latest American guidelines on valvular heart disease. Indeed, percutaneous repair techniques, particularly transcatheter edge-to-edge, have gained a broad experience and demonstrated to be safe and effective. However, given the complexity and heterogeneity of MV anatomy and pathology, transcatheter MV implantation (TMVI) has grown as a possible alternative to percutaneous MV repair. Current data about TMVI are still limited and come from different settings: valve-in-native MV, valve-in-valve (ViV), valve-in-ring (ViR), and valve-in-mitral annular calcification. Preliminary data are promising although several open issues still need to be addressed. This paper provides a comprehensive review of the available devices in the different clinical settings, to discuss potentialities, limitations, and future directions for TMVI.